Evaluation of Digital’s Role in Sustainable Built Environment - Theodore Wayne, Theodore Wayne; Chang Saar Chai, Chang Saar Chai; Shirly Siew Ling Wong, Shirly Siew Ling Wong; Fang Lee Lim, Fang Lee Lim; Kai Chen Goh, Kai Chen Goh; Abidin, Nur IzieAdiana (Pertanika, 2023)
The construction industry has been evolving, embracing the delicate balance between the Fourth Industry Revolution and sustainable construction to create a sustainable and resilient built environment. Integrating digital tools and technologies in a renowned conventional construction industry is challenging, mainly due to the complex interaction between heterogeneous but heuristic construction processes, building systems, and workflows in achieving a common goal. This study took the initiative to review digital tool adoption and its role in the sustainable built environment by examining the impact of digital adoption in a sustainable built environment in terms of societal and industry impacts. A quantitative analysis is conducted, collecting 63 industry practitioners analysed through regression analysis. The result reveals that energy conservation is the most significant element in the sustainable built environment, which brought the greatest impact on both society and industry in Malaysia. Based on the results, it is found that the digital adoption level in the Malaysian construction industry is still at a minimal level. Through the introduction of Indutry4wrd, National 4IR and Construction 4.0 Strategic Plan (2021–2025), the importance of digital tools and technologies is slowly being acknowledged. The result of the study is significant to benchmark the current digital tools adoption in the Malaysian sustainable built environment. Moreover